Broad Inclusive Salvation: The Logic of “Anonymous Christianity” - Gould, James B. (Philosophy & theology, 2008)
In this paper I defend three points: (1) God loves and desires the salvation of every human person, (2) saving grace is available outside of the Christian church to those who do not hear the gospel but pursue moral goodness and (3) most, if not all, human persons will be saved. I argue that soteriological restrictivism is logically incoherent since its two ideas—every person is loved by God and only those who hear and believe the Christian gospel can be saved—cannot both be true. Throughout I integrate insights from Karl Rahner’s notion of “anonymous Christianity.”